THE MECHANISM FOR THE IMPLEMENTATION OF DIGITAL EDUCATIONAL RESOURCES IN THE "ELEARNING" SYSTEM - Kudubayeva, Saule (European Scientific Journal, ESJ, 2014)
The problems of implementing e-learning through the integration of teaching and information and communication technologies that radically increase the effectiveness of training and massive quality education. Sets out requirements for the characteristics of the system being interconnections with adjacent systems for the storage and use of digital learning resources (DLRs). The requirements to be met by DLR, placed on the portal «elearning ».